Islamic commercial law : contemporariness, normativeness, and competence - Reda, Mohamed H. (Brill's Arab and Islamic Laws Ser., 2017)
Islamic Commercial Law: Contemporariness, Normativeness and Competence offers new perspectives on why for centuries Islamic commercial law has been perceived as arbitrary and unpredictable, and on its evolution to a contemporary, consistent, reliable and credible body of law. The book also examines why Western positivists have viewed Islamic commercial law in a simplistic or archaic religious framework and counters those arguments with an examination of its normative legal qualities. The work analyses the competencies of Fiqh (jurisprudence) for structuring new financial instruments, and restructuring conventional financial products more equitability.